Pengaruh Media Big Book terhadap Peningkatan Kemampuan Membaca Permulaan Siswa Kelas I di SD IT Al Ikhlas Gaya Baru III - Restu Lestari; Hanif Amrulloh; Lutfi Fadilah (Prodi Pendidikan Guru Sekolah Dasar, 2026)
This study aimed to determine the effect of Big Book media on the early reading skills of Grade I students at SD IT Al Ikhlas Gaya Baru III. The study employed a quantitative approach using a one-group pretest-posttest experimental design. The participants were all Grade I students (N = 13). Data were collected through early reading tests administered as pretest and posttest, then analyzed using descriptive statistics, a normality test, a paired- sample t-test, and N-Gain analysis. The results showed that the mean score increased from 59.69 on the pretest to 77.38 on the posttest. The normality test indicated that the data were normally distributed (p > 0.05). The paired-sample t-test showed a significant difference between pretest and posttest scores (t = -14.010, p < 0.001). In addition, the average N-Gain score was 0.44, which falls into the medium category, indicating that Big Book media was moderately effective in improving students’ early reading skills. Big Book media not only helped students recognize letters and words, but also increased their interest and engagement in reading activities. It can be concluded that the use of Big Book media was effective in improving the early reading skills of Grade I students.